Biomedical Waste Management-An Emerging concern in Medical practice. - Dr.Pradeep Kumar.R, Dr. Anita .M , Dr. Deepa S (Drugs and Cell Therapies in Hematology, 2021)
Biomedical waste management has become an important issue as it poses potential health risks. Proper handling, treatment and disposal of biomedical wastes play a vital role in hospital infection control management. Handling, segregation, disinfection, storage, transportation and final disposal of the waste are to be considered to prevent health hazards. Lack of concern, motivation, awareness, cost factor are some problems faced in the proper waste management.